Antibody response in Danish Jersey heifers to foot-and-mouth-disease vaccine - CHITRAVEL, V; PADMARAJ, A; SAYEED, S A; KORUTH, JOHNSI; RAMESH, R (The Indian Journal of Animal Sciences, 2013)
Danish Jersey heifers (pregnant) imported from Denmark were vaccinated with foot-and-mouth-disease (FMD) polyvalent (0, A22,C, Asia-I) vaccine. A booster dose was given on day 2·1. Primary and secoridary antibody responses were assessed by micro-serum neutralization test (microSNT). The animals did not have detectable level of antibody prior to vaccination supporting the fact that these animals were imported from FMD-free country and that they were neither exposed to infective virus nor to immunizing antigen. There was on set of antibody response on day 7 post-vaccination (PV), and the titres on day 21 PV were 1.58:1:0.4, 1.55±.03, 1.55±.03, 1:54±03 against types 0, A22, C and Asia-I viruses. The percentage of animals exhibiting protective titre (->1.5) on day 21 PV stood as 84, 88, 92 and 92 against types 0, A22, C and Asia-I respectively. After the boostef dose the titre attained maximum levels. viz. l.84±0.09, 1.81±0.08, t.84±0.09, 1.8 H:0.08 against types 0, A22, C and Asia-I, respectively, within a week. At the end of quarantine period, viz. day 40 PV or day 19 Post booster vaccination, the percentages of animals with protective titre (>-1.5 ) were 96, 98, 98 and 98 against types 0, A22, C and Asia-I respectively.